2010
DOI: 10.1186/1472-6882-10-77
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage preventive activity and antioxidant potential of plants used in Unani system of medicine

Abstract: BackgroundThere is increasing recognition that many of today's diseases are due to the "oxidative stress" that results from an imbalance between the formation and neutralization of reactive molecules such as reactive oxygen species (ROS) and reactive nitrogen species (RNS), which can be removed with antioxidants. The main objective of the present study was to evaluate the antioxidant activity of plants routinely used in the Unani system of medicine. Several plants were screened for radical scavenging activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 36 publications
7
96
2
1
Order By: Relevance
“…The phenol, flavonoid content, and DPPH scavenging activity, as well as the major essential oils present in CS, all contribute to its antioxidant properties, which may be the reason for its nephroprotective activity in the present study. A study by Kalim et al in 2010 also identified DPPH, hydroxyl ion, and superoxide scavenging properties (28). The results of the present study show possible nephroprotection offered by hydroalcoholic extract of CS at 150 mg/kg and 250 mg/kg doses for the prevention of AKI, as well as for the treatment of established kidney injuries.…”
Section: Discussionsupporting
confidence: 48%
“…The phenol, flavonoid content, and DPPH scavenging activity, as well as the major essential oils present in CS, all contribute to its antioxidant properties, which may be the reason for its nephroprotective activity in the present study. A study by Kalim et al in 2010 also identified DPPH, hydroxyl ion, and superoxide scavenging properties (28). The results of the present study show possible nephroprotection offered by hydroalcoholic extract of CS at 150 mg/kg and 250 mg/kg doses for the prevention of AKI, as well as for the treatment of established kidney injuries.…”
Section: Discussionsupporting
confidence: 48%
“…Although in these studies the contribution of NAAs to the pharmaceutical effect is questioned, the biofunctionality of some NAA containing plant extracts has been described. The antioxidant effects of Anacyclus pyrethrum and Spilanthes acmella have been demonstrated (Kalim et al, 2010;Wongsawatkul et al, 2008). Synthetic N-(1-oxo-1,3-dihydro-2-benzofuran-5-yl)alkylamide derivatives, preferably containing a fluorine or chlorine atom in their fatty acid part are claimed to preserve the antioxidant and strengthening effects of the skin (Boulle, 2008 Q4 ).…”
Section: Othersmentioning
confidence: 99%
“…. Valeriana wallichii has been reported for analgesic, 48 anti-inflammatory, [49][50] and antioxidant actions 51 .…”
mentioning
confidence: 99%